The Qwantify app dataset: A remote experience sampling study of desire, emotion, and well-being - Wilson-Mendenhall, Christine D.; Condon, Paul; Hasenkamp, Wendy; MacKerron, George; Quigley, Karen S.; Barrett, Lisa Feldman (Frontiers in Psychology, 2022)
Experiences of desire—the feeling of wanting to have, do, or experience something—are pervasive and varied. Recent theoretical advances draw attention to characterizing this variation. Thus, this study investigated experiences of desire in everyday life and co-occurring social, physical, and emotional states, including facets of emotional experiences known to be related to well-being (e.g., perceived loneliness and stress). The Qwantify app was designed to run a remote experience sampling study. Through the app, participants were randomly alerted during their daily life to report on their experience in the moment. During the data collection period, any individual could download the freely available Qwantify app and participate in the study, without providing identifying information or communicating with researchers. Similar to other remote experience sampling studies, an incentive for participants to engage in the study was unlocking visualizations of their own data. Over 600 participants downloaded the app, completed the sign-up process, and responded to at least one experience sampling alert. Approximately 40% of these participants went on to respond to 50 alerts. The purpose of this report is to describe this experience sampling dataset such that it can be used to test a variety of hypotheses, including hypotheses regarding individual differences.